2022
DOI: 10.1039/d2nr04285a
|View full text |Cite
|
Sign up to set email alerts
|

Sequential galvanic replacement mediated Pd-doped hollow Ru–Te nanorods for enhanced hydrogen evolution reaction mass activity in alkaline media

Abstract: High catalytic activity, long-term stability, and economical Pt-free catalysts for the hydrogen evolution reaction (HER) are required for the conversion of renewable energy systems. Noble nanomaterial Pt is a superior...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Significantly, we further demonstrated that the residual Se atoms on the surface could serve as a chemical linker to anchor the Pt nanoparticles to the carbon support (Figure 7D), greatly enhancing the stability of the electrocatalyst. Galvanic replacement synthesis involving nonmetallic substrates has also been reported for other materials, including Si (for Cu, Ag, Au, Pt, Pd, and Rh) 29 and Te (for Ir, 28 Rh, 38 and Ru 39 ), for the fabrication of various metal nanostructures. Most of the products were characterized by a rough surface because of the structural mismatch between the nonmetallic substrates and crystalline metals, similar to what was observed for the Se and Pt pair.…”
Section: Nonmetallic Substratesmentioning
confidence: 97%
See 1 more Smart Citation
“…Significantly, we further demonstrated that the residual Se atoms on the surface could serve as a chemical linker to anchor the Pt nanoparticles to the carbon support (Figure 7D), greatly enhancing the stability of the electrocatalyst. Galvanic replacement synthesis involving nonmetallic substrates has also been reported for other materials, including Si (for Cu, Ag, Au, Pt, Pd, and Rh) 29 and Te (for Ir, 28 Rh, 38 and Ru 39 ), for the fabrication of various metal nanostructures. Most of the products were characterized by a rough surface because of the structural mismatch between the nonmetallic substrates and crystalline metals, similar to what was observed for the Se and Pt pair.…”
Section: Nonmetallic Substratesmentioning
confidence: 97%
“…Galvanic replacement synthesis involving nonmetallic substrates has also been reported for other materials, including Si (for Cu, Ag, Au, Pt, Pd, and Rh) and Te (for Ir, Rh, and Ru), for the fabrication of various metal nanostructures. Most of the products were characterized by a rough surface because of the structural mismatch between the nonmetallic substrates and crystalline metals, similar to what was observed for the Se and Pt pair.…”
Section: Nonmetallic Substratesmentioning
confidence: 99%
“…In a typical GRR synthesis process, the template materials, ionic species, stoichiometry, and temperature , need to be considered carefully. Specifically, high temperature and long reaction time (typically hours) are often required to enable the GRR process and ensure the shape control. , Sequential GRR with multiple metal precursors enables the synthesis of trimetallic or multimetallic nanostructures, which are believed to show improved catalytic performance. However, the manipulation of sequential GRR processes makes the complicated processes even more intricate and time-consuming. Meanwhile, bimetallic systems often form seamless alloyed (intermetallic) shells, which impede further reaction with additional metal precursors .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, the high cost of noble metals is a severe deterrent to the development of cost-effective efficient catalysts. 11,12 For industrial use, developing electrocatalysts with great performance under industrially relevant conditions, including high current density, long working times, and extreme pressure and temperature, is crucial. 13 Great performance at industrially relevant current densities is necessary because a high current density (≥200 mA cm −2 ) means a high rate of hydrogen production, which can reduce capital expenditures and lead to profitable hydrogen production.…”
Section: Introductionmentioning
confidence: 99%